2021
DOI: 10.20944/preprints202105.0427.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular Senescence: Pathogenic Mechanisms in Lung Fibrosis

Abstract: :Pulmonary fibrosis is a chronic and fatal lung disease that significantly impacts the aging population globally. To date, anti-fibrotic, immunosuppressive, and other adjunct therapy demonstrate a limited efficacy. Advancing our understanding of pathogenic mechanisms of lung fibrosis provides a future path for the cure. Cellular senescence has gained substantial interest in the past decades due to the increased incidence of fibroproliferative lung diseases in the older age group. Furthermore, the pathologic st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 184 publications
(272 reference statements)
0
6
0
Order By: Relevance
“…Pulmonary fibrosis serves as a prevalent interstitial lung disorder featured by chronic nonspecific inflammation of the interstitial lung and deposition of collagen, resulting in lung function impairment, and severely impaired the health and life quality of patients [ 1 ]. Unlike other kinds of lung disorders, the mechanisms of the progression of pulmonary fibrosis are still unclear [ 2 ]. Pulmonary fibrosis presents a high mortality rate and has been identified as a “tumor-like disease” [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary fibrosis serves as a prevalent interstitial lung disorder featured by chronic nonspecific inflammation of the interstitial lung and deposition of collagen, resulting in lung function impairment, and severely impaired the health and life quality of patients [ 1 ]. Unlike other kinds of lung disorders, the mechanisms of the progression of pulmonary fibrosis are still unclear [ 2 ]. Pulmonary fibrosis presents a high mortality rate and has been identified as a “tumor-like disease” [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…All three groups reported their presence in fibrotic regions of IPF lungs; an increase of AT2 cells in the transitional state was invariably accompanied by an increase in myofibroblasts. Our PPI network analyses suggested that AT2 senescence and progenitor arrested state in the setting of a ViP/sViP-immune response (cytokine storm contributed by PBMCs) may support a SASP phenotype, which is a pathological feature of aging and IPF lung(88, 89). It is possible that fibroblasts/myofibroblasts also contribute to this vicious cycle of inflammation and AT2 dysfunction.…”
Section: Discussionmentioning
confidence: 91%
“…Consequences of “macrophageing” may be the reduced ability of the macrophages to remove other senescent cells and to interact with adaptive immune cells (including antigen presentation). It is worth mentioning that SASP is not only proinflammatory, but, especially at early stages of development of this phenotype, also immunosuppressive (due to secretion of TGF-β1 and TGF-β3), dampening the efficiency immune responses, as well as profibrotic, leading to more severe lung fibrosis ( Ito et al, 2017 , Nacarelli et al, 2019 , Parimon et al, 2021 ). These features very likely participate in increased severity of COVID-19 in the elderly.…”
Section: Cellular Senescence Immunosenescence and Inflammaging - How ...mentioning
confidence: 99%